2021
DOI: 10.1017/jns.2021.83
|View full text |Cite
|
Sign up to set email alerts
|

Maternal malnutrition and anaemia in India: dysregulations leading to the ‘thin-fat’ phenotype in newborns

Abstract: Maternal and child malnutrition and anaemia remain the leading factors for health loss in India. Low birth weight (LBW) offspring of women suffering from chronic malnutrition and anaemia often exhibit insulin resistance and infantile stunting and wasting, together with increased risk of developing cardiometabolic disorders in adulthood. The resulting self-perpetuating and highly multifactorial disease burden cannot be remedied through uniform dietary recommendations alone. To inform approaches likely to allevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 151 publications
2
3
0
Order By: Relevance
“…Greater mean suprailiac skinfold thickness in children exposed to GDM, despite lower mean weight, BMI and circumferences, may reflect altered fat distribution, and have implications for future metabolic risk [ 28 ]. This is consistent with the “thin-fat” phenotype described in other populations, where there is preferential growth of adipose tissue compared to fat-free lean mass in children exposed to hyperglycemia in-utero [ 40 42 ], compounded by maternal malnutrition [ 43 ]. Children exposed to the double burden of malnutrition at different points during pregnancy and their lifecourse, of both nutritional deficiency and dietary excess, are also known to have increased cardiometabolic risk [ 44 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Greater mean suprailiac skinfold thickness in children exposed to GDM, despite lower mean weight, BMI and circumferences, may reflect altered fat distribution, and have implications for future metabolic risk [ 28 ]. This is consistent with the “thin-fat” phenotype described in other populations, where there is preferential growth of adipose tissue compared to fat-free lean mass in children exposed to hyperglycemia in-utero [ 40 42 ], compounded by maternal malnutrition [ 43 ]. Children exposed to the double burden of malnutrition at different points during pregnancy and their lifecourse, of both nutritional deficiency and dietary excess, are also known to have increased cardiometabolic risk [ 44 ].…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have indicated that childhood skinfold thicknesses and circumferences can serve as proxy indicators of lipid and insulin dysregulation, and that differences in fat deposition, as reflected by BMI, circumferences and fat free mass, can be used to assess cardiometabolic risk [ 28 , 41 , 56 ]. This may indicate higher cardiometabolic risk in First Nations children even from early childhood, consistent with studies from other populations describing the ‘thin-fat’ phenotype [ 41 , 43 ].…”
Section: Discussionsupporting
confidence: 85%
“…8,9 Deficiency of these nutrients in the diet of a pregnant mother manifests in adverse effects on the fetus, including developmental defects (e.g., neural tube defects), growth abnormalities (growth restriction), 10 and are also associated with an increased risk of non-communicable diseases in later life. 11,12…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Deficiency of these nutrients in the diet of a pregnant mother manifests in adverse effects on the fetus, including developmental defects (e.g., neural tube defects), growth abnormalities (growth restriction), 10 and are also associated with an increased risk of non-communicable diseases in later life. 11,12 The Pune Maternal Nutrition Study (PMNS) is a communitybased pre-conceptional birth cohort started in 1993 based on Prof. Barker's theory. 13 It was set up in six villages near Pune to study maternal nutritional determinants of fetal growth and to study life-course evolution of the risk of diabetes and related traits in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of these nutrients in the diet of a pregnant mother manifests in adverse effects on the fetus, including developmental defects (neural tube defects, midline congenital defects etc. ), growth abnormalities (growth restriction) (Gernand et al, 2016), and are also associated with an increased risk of non-communicable diseases in later life (Deshmukh et al, 2013; Pandit et al, 2021).…”
Section: Introductionmentioning
confidence: 99%